Bond behaviour between crumb rubberized concrete and deformed steel bars. (December 2021) - Gravina, Rebecca J.; Xie, Tianyu; Roychand, Rajeev; Zhuge, Yan; Ma, Xing; Mills, Julie E.; Youssf, Osama
Abstract: This study presents a systematic investigation of the bond behaviour of rubberized concrete. The local and global bond behaviours of rubberized concrete are studied experimentally using concentric pull-out test and beam end test, respectively. The test parameters include concrete strength grade, bar embedded length, bar diameter and rubber content. In addition to the bond tests and the ancillary material property tests, six large-scale reinforced rubberized concrete beams are also tested under flexural bending to evaluate the influence of the alteration of bond behaviour owing to rubber incorporation on the flexural performance of the beams. The higher deformability of rubberized concrete compared to conventional concrete at each strength grade results in altered local and global bond behaviour, where the reduced peak bond stress and an increase in the slip at the peak bond stress are observed. The altered bond in conjunction with the other reduced mechanical properties of rubberized concrete subsequently led to a reduction in the flexural stiffness at the elastic stage and a reduction in ductility at the post-peak stage of a corresponding reinforced concrete beam containing rubber. The results of the mechanics-based and code-based models for predicting the development length for a reinforced bar in rubberized concrete indicated that the code-based model to design the anchorage length in rubberized concrete could be used with confidence.